Inovasi Pembelajaran dan Kepemimpinan dalam Kontribusi Pengabdian Program Mengajar di Universitas Sunan Giri Surabaya - Al Farochi, Mohammad Naufal; Sa’diyah, Siti Halimatus; Rahayu, Misye Adelia; Hardyansah, Rommy; Darmawan, Didit; Putra, Arif Rachman; Arifin, Samsul; J, Jahroni; Evendi, Wakid (Yayasan Daarul Huda Kruengmane, 2025)
Limited access to innovative educational methods and materials and lack of understanding of leadership among students are major problems in developing innovation in the learning process. The Teaching Program at Sunan Giri University Surabaya aims to provide solutions to these problems by equipping students with skills in creative teaching and leadership. The method used is to develop a combination of intensive training for students. The form of activities includes interactive learning and integrated leadership sessions with a focus on developing students' critical thinking and leadership skills. The results of this activity show an increase in the quality of student teaching and interest, as well as contributing to the development of the community around the campus.